2008
DOI: 10.1063/1.2837196
|View full text |Cite
|
Sign up to set email alerts
|

Strain and vacancy cluster behavior of vanadium and tungsten-doped Ba[Zr0.10Ti0.90]O3 ceramics

Abstract: Strain and vacancy clusters behavior of polycrystalline vanadium (V) and tungsten (W)-doped Ba[Zr0.10Ti0.90]O3, (BZT:2%V) and (BZT:2%W) ceramics obtained by the mixed oxide method was evaluated. Substitution of V and W reduces the distortion of octahedral clusters, decreasing the Raman modes. Electron paramagnetic resonance data indicate that the addition of dopants leads to defects and symmetry changes in the BZT lattice. Remnant polarization and coercive field are affected by V and W substitution due the ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…It was found that the environment of the ethylene glycol solution considerably influenced the shape formation of the YVO 4 :Ln crystals. latter to the f-f transitions within Dy 3+ 4 F 9 configuration [19,31]. The absorption of [VO 6 ] is ascribed to a charge transfer from the oxygen ligands (O 2− ) to the central vanadium atom (V 5+ ).…”
Section: Resultsmentioning
confidence: 98%
“…It was found that the environment of the ethylene glycol solution considerably influenced the shape formation of the YVO 4 :Ln crystals. latter to the f-f transitions within Dy 3+ 4 F 9 configuration [19,31]. The absorption of [VO 6 ] is ascribed to a charge transfer from the oxygen ligands (O 2− ) to the central vanadium atom (V 5+ ).…”
Section: Resultsmentioning
confidence: 98%
“…The effect of doping on microstructure and dielectric properties of BZT materials has been extensively studied to further improve their performance [21][22][23][24][25][26][27][28][29][30][31]. It has been indicated that the diffuseness of the phase transition and the degree of ferroelectric relaxor behavior were enhanced and the tunability was suppressed as the x value of (Ba 1−x Ln x )Zr 0.2 Ti 0.8−x/4 O 3 (x = 0.005-0.04, Ln = La, Sm, Eu, Dy, Y) ceramics increased [21].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the researches with this perovskite [16e18] have been mainly focused on the dielectric properties as well as on the phase transition from ferroelectric to relaxor. In this case, in order to improve the electrical properties, the BZT ceramics have been doped with different lanthanides, semi-metal and alkaline-earth metals, such as: niobium [19], boron [20,21], lithium [17], yttrium [22], copper [23], vanadium [24], tungsten [25], manganese [26], nickel [27], aluminium [28], bismuth [23,29], lanthanum [30], cerium [31], samariumeeuropiumedysprosium [32], erbium [33] and ytterbium [34].…”
Section: Introductionmentioning
confidence: 99%